A POSTCOLONIAL FEMINIST READING OF J. M. COETZEE’S WAITING FOR THE BARBARIANS (2000) - Mary Mensah; Emmanuel Mensah Bonsu (International Journal of Humanity Studies (IJHS), 2022)
Literary texts and kinds of research have reframed postcolonial experiences to capture several issues in society. On that note, Coetzee’s Waiting for the Barbarians has chalked many successes in gaining the attention of literary scholars to subject the text to interpretation using varied literary approaches, except postcolonial feminism. The postcolonial aspect of the feminist issues in the text is fundamental. The thrust of this paper is to analyse Coetzee’s Waiting for the Barbarians using the postcolonial feminist theory. Guided by three objectives, the study uses the qualitative content analysis method to interpret the text. From the analysis, the study reported that, while objectification and ‘othering’ are characteristic of the representation of females in the text, violence against them is constructed through fear and torture and resisted mainly through silence. Also, the mode of narration influences the presentation of the narrative to readers. Finally, the study offers implications for further research using other literary theories or approaches.